Freeze-dried multiscale porous nanofibrous three dimensional scaffolds for bone regenerations - Khoramgah, Maryam Sadat (Bioimpacts, 2020)
[Image: see text] Introduction: Simulating hydrophobic-hydrophilic composite face with hierarchical porous and fibrous architectures of bone extracellular matrix (ECM) is a key aspect in bone tissue engineering. This study focused on the fabrication of new three-dimensional (3D) scaffolds containing polytetrafluoroethylene (PTFE), and polyvinyl alcohol (PVA), with and without graphene oxide (GO) nanoparticles using the chemical cross-linking and freeze-drying methods for bone tissue application. The effects of GO on physicochemical features and osteoinduction properties of the scaffolds were evaluated through an in vitro study. Methods: After synthesizing the GO nanoparticles, two types of 3D scaffolds, PTFE/PVA (PP) and PTFE/PVA/GO (PPG), were developed by cross-linking and freeze-drying methods. The physicochemical features of scaffolds were assessed and the interaction of the 3D scaffold types with human adipose mesenchymal stem cells (hADSCs) including attachment, proliferation, and differentiation to osteogenic like cells were investigated. Results: GO nanoparticles were successfully synthesized with no agglomeration. The blending of PTFE as a hydrophobic polymer with PVA polymer and GO nanoparticles (hydrophilic compartments) were successful. Two types of 3D scaffolds had nano topographical structures, good porosities, hydrophilic surfaces, thermal stabilities, good stiffness, as well as supporting the cell attachments, proliferation, and osteogenic differentiation. Notably, GO incorporating scaffolds provided a better milieu for cell behaviors. Conclusion: Novel multiscale porous nanofibrous 3D scaffolds made from PTFE/ PVA polymers with and without GO nanoparticles could be an ideal candidate for bone tissue engineering as a 3D template.